Clinical Relevance and Immunohistochemical Patterns of Silent Pituitary Adenomas: 10 Years of Single-centre Experience - Akkus, Gamze; Karagun, BarıŦ#159; Çetinalp, Nuri E.; Açıkalın, Arbil; Evran, Mehtap; Sengöz, Sinem; Sert, Murat; Zorludemir, Suzan; Tetiker, Tamer (Current Medical Imaging, 2021)
Background: Silent pituitary adenomas are clinically non-functional (i.e., without clinically evident pituitary hormone production). Introduction: The aim of this study was to investigate subjects with silent pituitary adenomas for possible variations in their clinical status. Methods: A total of 102 patients who had undergone surgery for pituitary adenoma and had been diagnosed with silent pituitary adenoma was included in the study. The patients’ preoperative and postoperative hormonal parameters and magnetic resonance imaging (MRI) features were collected, and pathological specimens were re-evaluated. Results: Immunohistochemistry results of the 102 patients were as follows: hormone-negative adenomas (n=35) 35.5%; FSH+LH-positivity (n=32) 31.3%; ACTH-positivity (n=11) 10.7%; α-subunit- positivity (n= 9) 8.8%; prolactin-positivity (n=8) 7.8%; GH-positivity (n=6) 5.4%; and plurihormonal adenoma (n=1). The mean sizes of SGA, SGHA, and SCA were 28.0±12.7, 30.0±16.0, and 27.7±8.9mm (p>0.05), respectively. With the exception of silent gonadotroph adenomas (SGAs), female gender dominance was shown in patients with silent growth hormone adenoma (SGHA) and silent corticotroph adenoma (SCA). Although no clinical relevance was observed in relation to hormonal excess, preoperative GH (4.21±4.6, vs. 0.27±0.36 p=0.00) was slightly more elevated in SGHA than in GH-negative adenomas. Additionally, preoperative basal ACTH values (47.3±28.7 vs. 23.9±14.4, p=0.003) were also higher in SCA compared to the other types. Our findings revealed SCAs to be of more aggressive behaviour than SGHAs and SGAs due to invasiveness in radiological imaging, their elevated re-operation, and postoperative ACTH values. Conclusion: Silent pituitary adenomas represent a challenging diagnostic tumour group. Careful initial evaluation of patients with pituitary adenomas should consider any mild signs and symptoms of functionality, particularly in cases of GH- and ACTH-secreting adenomas.
Keywords: silent gonadotroph adenoma